Potential of Garlic Filtrate as An Alternative Anticoagulant for Whole Blood Samples - Ari Nuswantoro; Jessica Ningtyas Berlianti (Universitas Nahdlatul Ulama Surabaya, 2022)
Synthetic anticoagulants such as heparin, citric, and ethylenediaminetetraacetic acid (EDTA) are commonly used to prevent blood clots. In contrast, its widespread use in clinical laboratories is still constrained by price, its toxic nature, and its short shelf life. Therefore, an alternative material that is relatively cheap, non-toxic, and easy to obtain and process in a ready-to-use form is needed. Garlic contains allicin and ajoene, which are anti-platelet and anti-thrombogenic. This study’s aim is to explore the potential of garlic filtrate as an alternative anticoagulant. Blood from 16 individuals was used and separated into four groups: non-anticoagulant, 50 μL/mL garlic filtrate, 100 μL/mL garlic filtrate, and 150 μL/mL heparin, for a total of 64 treatments. The Lee and White method showed that non-anticoagulated blood had normal clotting times (mean 8 minutes and 56 seconds), whereas heparin plasma and garlic filtrate plasma had longer clotting times (more than 20 minutes); and this is statistically different based on the ANOVA test with a significance value (p) of 0.000 < 0.05. On spectrophotometric measurements, the levels of calcium ions in heparinized plasma and serum were 8.66 mg/dL and 8.52 mg/dL, respectively, while in garlic plasma filtrate of 50 μL/mL and 100 μL/mL were 4.13 mg/dL and 3.58 mg/dL, respectively; this is also statistically different based on the ANOVA test with a significance value of 0.000 < 0.05. The differences indicate that garlic filtrate can extend clotting time and reduce calcium ions therefore it is worth reviewing as an alternative anticoagulant.